Antiferromagnetic coupling of TbPc2 molecules to ultrathin Ni and Co films - Klar, David; Klyatskaya, Svetlana; Candini, Andrea; Krumme, Bernhard; Kummer, Kurt; Ohresser, Philippe; Corradini, Valdis; de Renzi, Valentina; Biagi, Roberto; Joly, Loic; Kappler, Jean-Paul; del Pennino, Umberto; et al. (Beilstein Journal of Nanotechnology, 2013)
The magnetic and electronic properties of single-molecule magnets are studied by X-ray absorption spectroscopy and X-ray magnetic circular dichroism. We study the magnetic coupling of ultrathin Co and Ni films that are epitaxially grown onto a Cu(100) substrate, to an in situ deposited submonolayer of TbPc2 molecules. Because of the element specificity of the X-ray absorption spectroscopy we are able to individually determine the field dependence of the magnetization of the Tb ions and the Ni or Co film. On both substrates the TbPc2 molecules couple antiferromagnetically to the ferromagnetic films, which is possibly due to a superexchange interaction via the phthalocyanine ligand that contacts the magnetic surface.
Keywords: magnetic anisotropy; magnetic coupling; single molecule magnets; X-ray absorption spectroscopy